Has Oxidative Stress any Role on Mechanisms of Aminophylline – Induced Seizures? An Animal Study - Roy, UK; Pal, M; Datta, S; Harlalka, S (Kathmandu University Medical Journal, 2015)
Background Aminophylline can trigger seizures in patients without known underlying epilepsy or added risk factor for seizure exacerbation in epilepsy. Most of these seizures are difficult to control and are underappreciated compared to other drug toxicities. Despite a long clinical history of aminophylline-induced seizures, relatively little is known about the underlying molecular mechanisms that contribute to methylxanthine-induced seizure generation. Objective The present study evaluated the possible involvement of free radicals in aminophylline induced seizures in rat. Method The rats were divided into two groups. The first group graded single doses of aminophylline from 100 to 300 mg/kg were administered intraperitoneally. On the basis of the results Aminophylline, a dose (300 mg/kg) producing tonic-clonic seizures and mortality in 100% animals was selected as control in the study. The second group were subjected to single antioxidant (Vitamin E or Vitamin C) or in combination for 45 days then single doses of aminophylline 300 mg/kg administered intraperitoneally to rats. Result Aminophylline induced convulsions in rats in a dose-dependent manner, and both incidence of seizure and mortality were maximum at 300 mg/kg and there was significant increase of free radical generation. But though pre-treatment with antioxidants showed differential attenuating effects on aminophylline induced free radical generation as we all known but they were very much ineffective in antagonizing aminophylline induced seizures and post-seizure mortality by any appreciable extent. Conclusion Though Aminophylline induces oxidative stress the results are suggestive that at least free radicals is not only cause of convulsiogenic effects and post-seizure mortality of aminophylline. Kathmandu University Medical Journal Vol.12(4) 2014; 269-274